An optimized dosing regimen of cimaglermin (neuregulin 1β3, glial growth factor 2) enhances molecular markers of neuroplasticity and functional recovery after permanent ischemic stroke in rats. Issue 3 (11th December 2015) - Iaci, Jennifer F.; Parry, Tom J.; Huang, Zhihong; Pavlopoulos, Elias; Finklestein, Seth P.; Ren, Jingmei; Caggiano, Anthony
Abstract : Cimaglermin (neuregulin 1β3, glial growth factor 2) is a neuregulin growth factor family member in clinical development for chronic heart failure. Previously, in a permanent middle cerebral artery occlusion (pMCAO) rat stroke model, systemic cimaglermin treatment initiated up to 7 days after ischemia onset promoted recovery without reduced lesion volume. Presented here to extend the evidence are two studies that use a rat stroke model to evaluate the effects of cimaglermin dose level and dose frequency initiated 24 hr after pMCAO. Forelimb‐ and hindlimb‐placing scores (proprioceptive behavioral tests), body‐swing symmetry, and infarct volume were compared between treatment groups (n = 12/group). Possible mechanisms underlying cimaglermin‐mediated neurologic recovery were examined through axonal growth and synapse formation histological markers. Cimaglermin was evaluated over a wider dose range (0.02, 0.1, or 1.0 mg/kg) than doses previously shown to be effective but used the same dosing regimen (2 weeks of daily intravenous administration, then 1 week without treatment). The dose‐frequency study used the dose‐ranging study's most effective dose (1.0 mg/kg) to compare daily, once per week, and twice per week dosing for 3 weeks (then 1 week without treatment). Dose‐ and frequency‐dependent functional improvements were observed with cimaglermin without reduced lesion volume. Cimaglermin treatment significantly increased growth‐associated protein 43 expression in both hemispheres (particularly somatosensory and motor cortices) and also increased synaptophysin expression. These data indicate that cimaglermin enhances recovery after stroke. Immunohistochemical changes were consistent with axonal sprouting and synapse formation but not acute neuroprotection. Cimaglermin represents a potential clinical development candidate for ischemic stroke treatment. © 2015 The Authors. Journal of Neuroscience Research Published by Wiley Periodicals, Inc. Abstract : Cimaglermin 0.1 and 1.0 mg/kg daily for 14 days significantly improved recovery in sensorimotor forelimb function compared with vehicle (top). Additionally, cimaglermin treatment significantly increased the expression of GAP43, a neural plasticity marker, in areas associated with the primary and secondary motor cortices in both hemispheres compared with vehicle (bottom).